(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2023)
In this article, the capture of two pregnant females of the Brazilian Guitarfish, Pseudobatos horkelii, is recorded. Although the species is Critically Endangered and it capture is prohibited, the illegal catches occur nevertheless.